PKM KELOMPOK PENGRAJIN PURUN DESA ARAPAYUNG SERDANG BEDAGAI - Sulaiman Lubis; Muhammad Alqamary; Dedy Husrizal Syah; Mukti Hamjah Harahap; Irfandi; Deo Demonta Panggabean (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2020)
Abstract This service program aims to help the efforts of the webbing purun craftsmen group of Ara Payung Village in increasing the Group's Knowledge and Skills to develop their business. As well as increasing the quality and quantity of products as well as product variations without eliminating the distinctiveness of cultural products of the Banjar people in Pantai Cermin District. Partners experienced include 1). Defective raw materials must be purchased from Langkat district 2). Production is still traditional; there is no touch. Technology is put in the middle of the road to be run over by vehicles 3). The drying process is still manual drying on the roadside without ignoring the cleanliness of materials 4). Management of business management is still traditional and centralized with a chairperson 5). Marketing only around mirror beaches and sometimes sold at beach attractions 6). Product packaging does not exist and still uses ordinary asoy plastic. Activities that have been given to purun and pandan handicraft businesses include 1). Training and assistance in nursery and planting methods using riverside and swamp media around the village 2). Handover of TTG equipment for flatters and purun splitters so that the product raw materials can be standard 3). They were drying using a heat storage tarpaulin so that the fabric dries quickly and is kept clean 4). Training and assistance in business management and administration of business financial accounting, 5). Providing packaging tools for packaging products.. Abstrak Tujuan Program pengabdian ini adalah membantu usaha kelompok pengrajin Anyaman purun Desa Ara Payung dalam meningkatkan Pengetahuan dan Keterampilan Kelompok mengembangkan usahanya. Serta meningkatkan kualitas dan kuantitas produk serta variasi produk tanpa menghilangkan ke khasan produk budaya Kaum Banjar di Kecamatan Pantai Cermin. Yang dialami mitra antara lain: 1). Bahan Baku tidak tercukupi harus dibeli dari kabupaten Langkat 2). Produksi masih tradisional belum ada sentuhan Teknologi di letakkan di tengah jalan agar dilindas oleh kendaraan 3). Proses Penjemuran masih manual di jemur di pinggir jalan dengan mengabaikan kebersihan bahan 4). Manajemen pengelolaan usaha masih tradisional dan tersentral dengan ketua 5). Pemasaran hanya di sekitar pantai cermin dan kadang dijual di objek wisata pantai 6). Kemasan Produk belum ada dan masih menggunakan plastik asoy biasa. Kegiatan yang telah diberikan kepada usaha kerajinan purun dan pandan antara lain : 1). Pelatihan dan Pendampingan cara pembibitan dan penanaman menggunakan media pinggir sungai dan rawa disekitar desa 2). Penyerahan Alat TTG untuk pemipih dan pembelah purun agar bahan baku produk dapat standart 3). Penjemuran dengan menggunakan terpal penyimpan panas agar bahan cepat kering dan trjaga kebersihanny 4). Pelatihan dan pendampingan manajemen usaha serta administrasi pembukuan keuangan usaha, 5). Pemberian alat Packaging produk kemasan.